m6A demethylase FTO and osteoporosis: potential therapeutic interventions - Huang, Mei; Guo, Jianmin; Liu, Lifei; Jin, Haiming; Chen, Xi; Zou, Jun (Frontiers in Cell and Developmental Biology, 2023)
Osteoporosis is a common bone disease, characterized by a descent in bone mass due to the dysregulation of bone homeostasis. Although different studies have identified an association between osteoporosis and epigenetic alterations in osteogenic genes, the mechanisms of osteoporosis remain unclear. N6-methyladenosine (m6A) modification is a methylated adenosine nucleotide, which regulates the translocation, exporting, translation, and decay of RNA. FTO is the first identified m6A demethylase, which eliminates m6A modifications from RNAs. Variation in FTO disturbs m6A methylation in RNAs to regulate cell proliferation, differentiation, and apoptosis. Besides, FTO as an obesity-associated gene, also affects osteogenesis by regulating adipogenesis. Pharmacological inhibition of FTO markedly altered bone mass, bone mineral density and the distribution of adipose tissue. Small molecules which modulate FTO function are potentially novel remedies to the treatment of osteoporosis by adjusting the m6A levels. This article reviews the roles of m6A demethylase FTO in regulating bone metabolism and osteoporosis.